2021
DOI: 10.1186/s12884-021-03757-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal overweight but not paternal overweight before pregnancy is associated with shorter newborn telomere length: evidence from Guangxi Zhuang birth cohort in China

Abstract: Background Telomere length (TL) is variable at birth and is inversely associated with body mass index (BMI) in adulthood. A growing number of evidences suggested that a higher maternal pre-pregnancy BMI results in adverse offspring health outcomes, especially shorter newborn TL. However, a newborn’s genetic endowment is equally derived from both parents, the association between parental pre-pregnancy BMI and newborn TL has been rarely discussed. We aimed to determine the association between par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Researchers from the University of Hasselt in Belgium found that (Martens et al, 2016) a significant inverse relationship between maternal pre-pregnancy BMI and newborn telomere length, for every one-unit increase in BMI, infant telomeres shortened by an estimated 50 base pairs after adjusting for various maternal and newborn characteristics. A cohort study (Wei et al, 2021) from China also found a relationship between prematernal overweight and shorter neonatal telomeres. The specific mechanisms still require elucidation but could involve pathways influencing metabolism, growth factors, and inflammation (Movérare-Skrtic et al, 2009;Xu et al, 2014;Lv et al, 2022).…”
Section: Discussion Mechanismmentioning
confidence: 85%
“…Researchers from the University of Hasselt in Belgium found that (Martens et al, 2016) a significant inverse relationship between maternal pre-pregnancy BMI and newborn telomere length, for every one-unit increase in BMI, infant telomeres shortened by an estimated 50 base pairs after adjusting for various maternal and newborn characteristics. A cohort study (Wei et al, 2021) from China also found a relationship between prematernal overweight and shorter neonatal telomeres. The specific mechanisms still require elucidation but could involve pathways influencing metabolism, growth factors, and inflammation (Movérare-Skrtic et al, 2009;Xu et al, 2014;Lv et al, 2022).…”
Section: Discussion Mechanismmentioning
confidence: 85%
“…Lazarides et al found shorter TL in newborns from mothers with a pro-inflammatory state [ 54 ], and Wei et al reported a relationship between maternal smoking and short TL in children [ 55 ]. Studies have, furthermore, shown an inverse relationship between the BMI of the mother before pregnancy and the TL of the child [ 56 , 57 ], as well as between gestational diabetes and shorter TL in offspring [ 58 , 59 , 60 ], although these studies did not control for the TL of the mother. McAninch et al also found an association between metabolic syndrome in pregnancy and reduced TL in children at age 10 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of the Guangxi Zhuang Birth Cohort (GZBC), an ongoing prospective birth cohort study of the Zhuang population in Guangxi province, China. The details of this cohort have been described previously [18,19]. In the present study, we extracted cohort data for 994 pregnant women with live singletons from January 2016 to December 2017 for AFB1 exposure in early pregnancy.…”
Section: Study Populationmentioning
confidence: 99%